2017
DOI: 10.1504/ijlc.2017.10007616
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education revisited - perceived entrepreneurial role models increase perceived behavioral control

Abstract: Relying on Bandura's (1986) social learning theory, Ajzen's (1988) theory of planned behaviour (TPB), and Dyer's (1994) model of entrepreneurial careers, this study aims to highlight the potential of entrepreneurial role models to entrepreneurship education. The results suggest that entrepreneurial courses would greatly benefit from real-life experiences, either positive or negative. The results of regression analysis based on 426 individuals, primarily from Austria, Finland, and Greece, show that role models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…As hypothesized, entrepreneurial passion positively influenced entrepreneurial intention, in line with the findings of other researchers who researched samples not affected with disabilities (e.g. Iyortsuun and Shakpende, 2022;Murad et al, 2021;Karimi, 2020;Syed et al, 2020;Fellnhofer, 2017;Liu and Gu, 2017;Cardon, 2009). This finding helps to move the literature forward and addresses a question posed by Jammaers and Zanoni (2020) as to whether passion plays an influential role in entrepreneurship in those with disabilities, given the multiple barriers they face to enter entrepreneurship.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As hypothesized, entrepreneurial passion positively influenced entrepreneurial intention, in line with the findings of other researchers who researched samples not affected with disabilities (e.g. Iyortsuun and Shakpende, 2022;Murad et al, 2021;Karimi, 2020;Syed et al, 2020;Fellnhofer, 2017;Liu and Gu, 2017;Cardon, 2009). This finding helps to move the literature forward and addresses a question posed by Jammaers and Zanoni (2020) as to whether passion plays an influential role in entrepreneurship in those with disabilities, given the multiple barriers they face to enter entrepreneurship.…”
Section: Discussionsupporting
confidence: 85%
“…According to Iyortsuun and Shakpande (2022) the positive perspective of passion drives individuals to participate in valuable activities. In the studies conducted by Fellnhofer (2017) and Liu and Gu (2017), it was concluded that entrepreneurial passion facilitates entrepreneurial intention. This means that individuals who love business and see it as an important part of their lives will make efforts to start their own businesses.…”
Section: Entrepreneurial Passionmentioning
confidence: 99%
“…They use passion as an indication of students' motivation for entrepreneurship since passion is a solid energizing driver of entrepreneurial behavior reflected in a willingness to work hard, persistently and with dedication to realizing business ideas. Fellnhofer (2017) finds that entrepreneurial role models in EE influence students' entrepreneurial intention, mediated by the entrepreneurial passion that is transferred from the entrepreneurial role models whom students meet during the EE intervention. Although current research thus points to the possibility of enhancing student entrepreneurial passion through EE, Lackéus and Sävetun (2019) argue that while EE seems to be able to increase general passion, it is more challenging to increase specific entrepreneurial passion.…”
Section: Unpacking the Content Of A Model For The Entrepreneurial Min...mentioning
confidence: 94%
“…Successful entrepreneurs are distinguished by their passion (Fellnhofer, 2017). Entrepreneurial passion is a critical component in the development of individual motivation and desire.…”
Section: Entrepreneurial Passion Social Entrepreneurial Self-efficacy...mentioning
confidence: 99%